Courtroom modifications for child witnesses law and science in forensic evaluations - Hall, Susan R. (American Psychological Association, 2008)
"In the 1980s, an upsurge in public awareness and media attention contributed to a significant increase in the numbers of child abuse and neglect incidents reported to law enforcement and child protection agencies. Because of the psychological trauma and distress that the child may have experienced prior to trial and the additional negative psychological sequelae that some children could experience as a result of courtroom confrontation with the alleged abuser, the courts fashioned specific rules regarding modifications to protect vulnerable child witnesses. Mental health professionals can provide forensic assessment and testimony on the need for and types of modifications that would be most appropriate. This book provides a structure for conducting courtroom modification evaluations for allegedly abused child witnesses and for providing related expert testimony. The authors review U.S. laws regarding courtroom modifications for these children, consider the scientific basis for courtroom modifications that implicate the defendant's confrontation right, describe the clinical manifestations of trauma and emotional distress in allegedly abused children that might affect their ability to testify, and assist clinicians in choosing appropriate trauma assessment instruments. They also provide guidelines for the competent conduct of courtroom modification evaluations in the present and recommendations for future directions in research, practice, and policy to ensure fair treatment for both alleged witnesses and defendants in modification hearings"--Cover. (PsycINFO Database Record (c) 2008 APA, all rights reserved)
Keywords: Forensic Sciences; Child Psychology; Child witnesses / United States; Examination of witnesses / United States; Conduct of court proceedings / United States / Psychological aspects; Forensic psychology / United States; Forensic sciences / United States; Kind; Aussagepsychologie